Lipids and Skin Health 2014
DOI: 10.1007/978-3-319-09943-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Wax Esters: Chemistry and Biosynthesis

Abstract: Wax esters are unique surface lipids found on the surface of terrestrial organisms. After a brief review of the composition, the mechanisms used in their biosynthesis by sebaceous glands are summarized. The molecular biology of biosynthesis of methyl-branched, short chain and very long chain acids, and the biochemical mechanism of the loss of the carboxyl carbon of the elongated very long chain acids to generate alkanes are reviewed. The molecular biology of biosynthesis of the major types of molecules contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 107 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…It is generally assumed that preening itself ( Goldstein, 1988 ) and the synthesis of predominantly waxy compounds into preen secretions are energy-demanding processes ( Sweeney et al, 2004 ; Kolattukudy, 2015 ) and therefore only individuals in good physical condition may fully invest in the production of preen secretions. This has been supported by studies that have found reduced preen gland volume in ­immunocompetent individuals ( Piault et al, 2008 ; Moreno-Rueda, 2015 ), individuals with coccidian and malaria infection ( Pap et al, 2013 ; Magallanes et al, 2016 ), higher microbial loads in plumage ( Jacob et al, 2014 ; Fulop et al, 2016 ) or having poor body condition ( Moreno-Rueda, 2010 , 2015 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that preening itself ( Goldstein, 1988 ) and the synthesis of predominantly waxy compounds into preen secretions are energy-demanding processes ( Sweeney et al, 2004 ; Kolattukudy, 2015 ) and therefore only individuals in good physical condition may fully invest in the production of preen secretions. This has been supported by studies that have found reduced preen gland volume in ­immunocompetent individuals ( Piault et al, 2008 ; Moreno-Rueda, 2015 ), individuals with coccidian and malaria infection ( Pap et al, 2013 ; Magallanes et al, 2016 ), higher microbial loads in plumage ( Jacob et al, 2014 ; Fulop et al, 2016 ) or having poor body condition ( Moreno-Rueda, 2010 , 2015 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%